Surgical treatment of mitral valve diseases in combination with massive thrombosis of left atrium: treatment at hospital period - Popov, V. V.; Mnischenko, V. I.; Vitovskyi, R. M. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Peculiarities of surgical treatment of mitral valve disease complicated with massive thrombosis of left atrium with cardiopulmonary bypass was examined. Analyzed group consists of 334 patients operated from 1984 y. till 2014 y. Massive thromboses of left atrium was definited in patients with volume of thrombotic masses was more than 1/3 of hole volume of left atrium not caunted volume of auriculum. Mitral stenoses clear or predominated was marked in all cases. There were 142 (39,8%) males and 202 (60,2%) females. Average age of patients was 57,2±5,2 (19–70) yy. All patients belong to IY NYHA class. Etiological cause of valve defect was rheumatic fever. Average being of permanent form of atrial fibrillation was 4,1±0,8 yy. The following procedures were performed during operation: isolated mitral valve replacement (n=255), isolated mitral valve replacement + annuloplasty tricuspid valve by Amosov–de Vega (n=47), isolated open mitral commisurothomy (n=28), isolated open mitral commisurothomy + annuloplasty tricuspid valve by Amosov–de Vega (n=4). The optimum variance of surgical treatment of massive thromboses of left atrium is removing removing basement of thrombotic formation at the left atrium and ligation of auriculum of the left atrium. Hospital mortality during period from 1999 to 2014 y. was 4.8%. Hospital mortality in cases of mitral valve replacement was 6.1% and in cases of open mitral commisurothomy – 0%. Reasons of fatal outcomes were: acute cardiac and vascular failure (n=4), central nervous system injury (thromboembolism) (n=3), multyorgan failure (n=3), bleeding (n=4). Specific lethal complications – thrombembolic were marked especially in patients with absence removing of thrombotic basement of the left atrium and ligation of left atrium`s auriculum.